ÅEs posible la separación de los alcantarillados de aguas residuales y de aguas lluvia en ciudades colombianas? (2017)
Nowadays, the sewerage system is considered as a basic service just like the access to energy, drinkable water, waste disposal among others. All the basic services are the basis on which it could be determined the quality of life of the people and are of vital importance for the correct economic, social and environmental development of a specific place. Therefore, it is fundamental to choose the most appropriate system of sanitation that meets the established objectives to maintain an harmony with the environment and to protect human health. In this paper, a brief description is given of existing conventional sewer systems, their advantages and disadvantages, and the most appropriate option according to the characteristics of the main cities of Colombia.--Tomado del Formato de Documento de Grado.